Effects of Socioeconomic Status of Parents on Educational Attainment of the Undergraduates of the University of Jaffna: A Comparative Study on Arts and Law Students - Nithlavarnan, A.; Sinnathamby, M. (JUICE- 2012 University of Jaffna, 2012)
This study has attempted to describe and explain the relationship between parents’ socioeconomic status and undergraduates’ educational attainment using a case study approach. The objectives of the study were: to estimate the relationship between parents’ educational level, income level and occupations; with undergraduates’ educational performance in Faculty of Arts, University of Jaffna in the year 2011. A convenient sample of arts and law students attending a socioeconomically diverse University of Jaffna was utilized as the basis for conducting an undergraduate student survey (n=40). Data for the study were collected through the use of questionnaires for undergraduates, interview with lecturers and head of the Departments, documentary analysis of the university records and observation. Both qualitative and quantitative methods of study were used. The researchers used Tables, charts and Pearson’s correlation to describe and analyze quantitative data while qualitative data were analyzed on the basis of themes. The results showed that there was a positive correlation between the parents’ level of education, income and occupation with pupil’s educational performance. Students from higher socioeconomic backgrounds tend to have higher levels of under graduate academic achievement because they enter university with cultural capital that they acquired prior to university. This study recommends that parents should continue to improve on their education levels through adult education programmes. Secondly, undergraduates from low socioeconomic backgrounds should try to persevere through financial hardships and remain in university because schooling eventually has a redeeming effect on their poor plight. Lastly, undergraduates who obtain low grades should be helped to develop academic curiosity in fields which are more relevant to them. Graduate students can become academically liberated from the cultural effects of their socioeconomic origins.
Keywords: Educational Attainment; Socioeconomic Status,; Undergraduates